Factors influencing the development of the cashless payment system: Comprehending the function of the involved participants - Moutusi Tanha; Md. Mohibul Alam Dolon; Al-Amin Al-Amin; Nusrat Afrin Nadi; Md. Monirul Islam; Md. Hazrat Ali (goodwood publishing, 2024)
Purpose: The prevalence of cashless payments has increased globally owing to their myriad benefits. Furthermore, the use of cashless payments has also increased. Nevertheless, there is a need for more comprehensive research on the acceptance and current methodologies of cashless transactions. This study aims to gain a thorough understanding by identifying the entities involved and their pivotal functions in the payment ecosystem. Research Methodology: This report seeks to answer two research questions: i) Which factors are involved in the cashless payment ecosystem? What key elements influence the players in adopting a cashless payment ecosystem? Six key ecosystem players and their influencing elements were identified by comprehensively evaluating 63 publications published between 2015 and 2021. Results: Several benefits are associated with cashless payments, which have led to their growing popularity worldwide. Furthermore, during the COVID-19 epidemic, there was a significant increase in the use of cashless payment methods. Limitations: On the other hand, more holistic studies on the widespread use of cashless payment methods and their respective modern behaviors are needed. Contribution: In addition to providing a foundation for further empirical research, this study contributes to resolving adoption-related concerns. Novelty: This study’s original approach to understanding the various elements driving cashless payment system development by focusing on participant roles and functions is unique. Unlike previous studies, this study examines human dynamics rather than technology or regulatory issues.